2020
DOI: 10.3233/prm-190620
|View full text |Cite
|
Sign up to set email alerts
|

In-clinic event related potentials after sports concussion: A 4-year study

Abstract: PURPOSE: Electrophysiological event-related potentials (ERP's) have been reported to change after concussion. The objective of this study is to use a simple 2-tone auditory P300 ERP in routine clinical settings to measure changes from baseline after concussion and to determine if these changes persist at return to play when other standard measures have normalized. METHODS: Three-hundred sixty-four (364) student athletes, aged 17-23 years, participating in contact sports were tracked over consecutive years. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Studies consistently found lower resting EEG power in one or more frequency bands (ranging from delta to gamma) post-SRC,73–75 with SRC-related effects potentiated in standing (vs seated) positions 73 74. Similarly, seven studies found altered amplitudes of numerous ERPs to auditory and visual stimuli after SRC,76–82 with all but one80 finding lower amplitude in SRC (vs non-SRC) groups and concussed athletes with more severe symptoms. P3/P300 was the most commonly studied ERP76–78 80–82; others were N1, P2, N4 and a brainstem potential to speech sounds (frequency following response (FFR)) 77 79 80.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies consistently found lower resting EEG power in one or more frequency bands (ranging from delta to gamma) post-SRC,73–75 with SRC-related effects potentiated in standing (vs seated) positions 73 74. Similarly, seven studies found altered amplitudes of numerous ERPs to auditory and visual stimuli after SRC,76–82 with all but one80 finding lower amplitude in SRC (vs non-SRC) groups and concussed athletes with more severe symptoms. P3/P300 was the most commonly studied ERP76–78 80–82; others were N1, P2, N4 and a brainstem potential to speech sounds (frequency following response (FFR)) 77 79 80.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, seven studies found altered amplitudes of numerous ERPs to auditory and visual stimuli after SRC,76–82 with all but one80 finding lower amplitude in SRC (vs non-SRC) groups and concussed athletes with more severe symptoms. P3/P300 was the most commonly studied ERP76–78 80–82; others were N1, P2, N4 and a brainstem potential to speech sounds (frequency following response (FFR)) 77 79 80. Studies have been mixed in whether80 82 or not76 81 ERP latency was associated with SRC.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…19 Numerous studies have reported ERP-related changes years after mTBI, even after neuropsychological measures became normal. [20][21][22] In these studies, changes in latency and amplitudes of P300, N2, and other components of the time-locked ERP were abnormal even when reaction time and accuracy on cognitive tasks have improved. 23,24 Palacios et al demonstrated neurite density loss at 6 months compared with 2 weeks after mTBI, in patients with or without significant recovery of neuropsychological measurements during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…The acute concussion data and the control group for this study were from a previous study that followed athletes over the course of up to four sports seasons and at five different sites [ 32 ]. The injury groups were compared to the pre-injury baselines (to get a sense of trajectory), and a reference group was taken from pre-season baselines of 120 subjects who were not part of the acute concussion group and who had no history of previous concussion.…”
Section: Subjectsmentioning
confidence: 99%